Ligands of Biological and Environmental Interest as Sequestering Agents for Fe3+ in Aqueous Solution: A Speciation Study of Natural Fluids - Anna Irto; Ileana Ielo; Clemente Bretti; Francesco Crea; Concetta De Stefano; Rosalia Maria Cigala (Molecules)
The interactions of Fe3+ with some ligands (Tranexamic (TXA−), Indole-3-acetic (IAA−), and Aminomethylphosphonic (AMPA2−) acids) of biological and environmental interest were studied. The speciation studies were performed in NaNO3(aq) and NaCl(aq) using potentiometric and, only for IAA−, spectrophotometric titrations at T = 298.15 K and 0.01 ≤ I/mol dm−3 ≤ 1.0. The proposed speciation models are as follows: Fe(TXA)H3+, Fe(TXA)2+, Fe(TXA)(OH)+, and Fe(TXA)(OH)2(aq) for TXA−; Fe(IAA)2+ for IAA−; and Fe(AMPA)H23+, Fe(AMPA)H2+, and Fe(AMPA)+ for AMPA2−. A comparison of logβ for the common FeL species gives logβFeIAA = 6.56 and logβFeAMPA = 14.84 (at I = 1.00 mol dm−3 and T = 298.15 K), suggesting that AMPA2− has a higher complexing ability towards Fe3+ than IAA−. The dependence on the ionic strength of the formation constants was modeled by means of a Debye–Hückel type equation and the SIT model, whilst the sequestering ability of the investigated ligands towards Fe3+ was quantified at various pHs, ionic strengths, and in the different supporting electrolytes by means of an empirical pL0.5 parameter. To complete this study of the behavior of the different Fe3+/ligand systems, various simulations in biological fluids and natural waters were conducted.